(untitled) (Journal of Medical & Health Sciences Review, 2025)
Chikungunya virus (CHIKV) spread by Aedes mosquitoes, is a re-emerging arboviral illness characterized by fever, skin rash and body pain that frequently endures beyond the acute phase. Treatment based on symptomatic management due to the absence of particular antiviral drug or vaccine. This constraint has stimulated the investigation of natural herbs possessing antiviral, anti-inflammatory and immunomodulatory properties which include Allium sativum (AS01), Curcuma longa (CL02), Aegle marmelos (AM03), Aloe vera (AV04), Zingiber officinale (ZO05) and Trachyspermum ammi (TA06). All these natural herbs have significant potential in mitigating inflammation, oxidative stress and systemic symptoms. Also study other species such as Andrographis paniculata and Tinospora cordifolia potential in alleviating CHIK symptoms. Although evidence endorses their complimentary function, safety issues underscore the necessity for standardization and clinical validation. A comprehensive strategy that merges pharmaceutical treatment with established herbal drugs may offer durable solutions for CHIK management.